Feed-forward control of a vehicle with single-wheel actuators - Moseberg, Jan-Erik; Roppenecker, Günter (19th IFAC World Congress on International Federation of Automatic Control, IFAC 2014, 2014)
For the horizontal motion of a vehicle with single-wheel actuators a model-based feed-forward control is derived. Using the accelerator and brake pedal position as well as the steering wheel angle, the feed-forward control generates a desired vehicle motion together with appropriate longitudinal and lateral forces on the vehicle mass and a corresponding yaw moment. Since no detailed vehicle model, e.g., the single-track model, is required it is possible to tune the horizontal vehicle dynamics arbitrarily without changing the vehicle's geometry. Subsequently, the obtained forces and the yaw moment are allocated to the eight horizontal tire forces. Since the vehicle considered is over-actuated a secondary objective, i.e., the safety maximization, can be pursued in addition to realizing the desired vehicle motion. Solving this optimization problem numerically in a real vehicle is time-critical, so an analytical solution is introduced.
Keywords: Control architectures in automotive control; Nonlinear and optimal automotive control; Vehicle dynamic systems

Horizontal vehicle motion control with single-wheel chassis actuators - Moseberg, Jan-Erik; Roppenecker, Günter (At-Automatisierungstechnik, 2014)
This paper presents a model-based control strategy for the horizontal motion of a vehicle with singlewheel chassis actuators. Itsmain purpose is the realization of a desired vehiclemotion, described by the vehicle's longitudinal and lateral acceleration as well as its yaw rate, by adjusting all four wheels separately. In doing so the redundant wheel actuators are used to maximize the driving safety. The approach results in a feedforward and feedback control structure which is only dependent on variables that can be measured with sensors used in a conventional vehicle.
Keywords: Automotive control; Horizontal vehicle dynamics; Model-based control; Nonlinear control; Single-wheel chassis actuators

Robust cascade control for the horizontal motion of a vehicle with single-wheel actuators - Moseberg, Jan-Erik; Roppenecker, Günter (Vehicle System Dynamics, 2015)
The article presents a cascade control for the horizontal motion of a vehicle with single-wheel actuators. The outer control loop for the longitudinal and lateral accelerations and the yaw rate ensures a desired vehicle motion. By a combination of state feedback control and observer-based disturbance feedforward the inner control loop robustly stabilises the rotating and steering motions of the wheels in spite of unknown frictions between tyres and ground. Since the three degrees of freedom of the horizontal motion are affected by eight tyre forces, the vehicle considered is an over-actuated system. Thus additional control objectives can be realised besides the desired motion trajectory as, for example, a maximum in driving safety. The corresponding analytical tyre force allocation also guarantees real-time capability because of its relatively low computational effort. Provided suitable fault detection and isolation are available, the proposed cascade control has the potential of fault-tolerance, because the force allocation is adaptable. Another benefit results from the modular control structure, because it allows a stepwise implementation. Besides, it only requires a small number of measurements for control purposes. These measurements are the rotational speeds and steering angles of the wheels, the longitudinal and lateral acceleration and the yaw rate of the vehicle.
Keywords: 4-wheel-drive; 4-wheel-steer; chassis control systems; control allocation; robust control